Enhancing reintegration of juvenile delinquents through creativity in art therapy - Miklósi, Márta (Creativity Studies, 2026)
For juvenile offenders, engaging in creative activities supports adaptation to their particular life situation by diverting attention from existing difficulties, contributing to a gradual stabilisation of the emotional system and making less salient feelings of isolation. In this study, we will look at the possibilities of art therapy for juvenile offenders and its positive effects, focusing on visual arts. We explore the conceptual background of the topic, examine the positive effects of these activities, and present important practical initiatives. Based on the findings of the literature and the initiatives studied, the positive outcomes of art therapy are wide-ranging, not only contributing to the development of specific skills, but also facilitating emotional expression and increasing self-esteem. For individuals who have lower communication skills, lower self-esteem, and poorer academic performance, art therapy programmes can be particularly beneficial and provide opportunities for learning and development. The literatures confirm that it is an excellent tool for preventing secondary desistance, so it is not only in the interest of the young people concerned, but also of society as a whole to support these programmes.